2022
DOI: 10.1186/s12888-022-04295-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of logo-therapy on disease acceptance and self-awareness of patients undergoing hemodialysis; a pre-test-post-test research

Abstract: Background Acceptance is considered a key variable in chronic diseases such as chronic renal failure. To achieve adaptation and acceptance, people face obstacles, and identifying these obstacles primarily requires self-awareness. logo-therapy can help a person achieve this goal. To this end, this study aimed to investigate the effect of logo-therapy on disease acceptance and self-awareness of patients undergoing hemodialysis referred to a medical centers supervised by Kerman medical science uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(46 reference statements)
0
1
0
1
Order By: Relevance
“…La logoterapia es una propuesta de origen psicológico, se ha encontrado útil con problemas de adicción al alcohol (McInerney et al, 2021) drogas, depresión, ansiedad, psicosis, duelo y desesperación (Russo-Netzer & Ameli, 2021); sin embargo, viene incursionando de manera imponente en el campo de la medicina, en el cual, recientes investigaciones demuestran que la logoterapia ayuda a reducir comportamiento de estrés, ansiedad, depresión; mejorando la calidad de vida en pacientes con enfermedades crónicas, como el cáncer (Beuselinck, 2021); insuficiencia renal crónica (Mehrizi et al, 2022), cardiovasculares (Ghasemi et al, 2022), cirugía cardiaca (Alavi et al, 2022), cáncer de mama (Raji Lahiji et al, 2022); diabetes (Bahar et al, 2021); reduciendo su mortalidad. Así mismo, la logoterapia se aplica en situaciones críticas para el cuidado de enfermos terminales o críticos que a veces desesperados, desean renunciar a la vida, pidiendo la eutanasia (Haugan & Dezutter, 2021).…”
Section: Resultados Y Discusiónunclassified
“…La logoterapia es una propuesta de origen psicológico, se ha encontrado útil con problemas de adicción al alcohol (McInerney et al, 2021) drogas, depresión, ansiedad, psicosis, duelo y desesperación (Russo-Netzer & Ameli, 2021); sin embargo, viene incursionando de manera imponente en el campo de la medicina, en el cual, recientes investigaciones demuestran que la logoterapia ayuda a reducir comportamiento de estrés, ansiedad, depresión; mejorando la calidad de vida en pacientes con enfermedades crónicas, como el cáncer (Beuselinck, 2021); insuficiencia renal crónica (Mehrizi et al, 2022), cardiovasculares (Ghasemi et al, 2022), cirugía cardiaca (Alavi et al, 2022), cáncer de mama (Raji Lahiji et al, 2022); diabetes (Bahar et al, 2021); reduciendo su mortalidad. Así mismo, la logoterapia se aplica en situaciones críticas para el cuidado de enfermos terminales o críticos que a veces desesperados, desean renunciar a la vida, pidiendo la eutanasia (Haugan & Dezutter, 2021).…”
Section: Resultados Y Discusiónunclassified
“…Batthyany and Guttmann (2006) examined more than 600 studies applying the logotherapy approach, who concluded that many studies proved the efficacy of logotherapy. Logotherapy is a proven intervention method with various problems in different life stages of individuals with posttraumatic stress disorder (de Moklebust, 2016), parents of children with Asperger's syndrome (Pakenham et al, 2004), patients (Julom & Guzman, 2013), those with chronic illness (Mehrizi et al, 2022), married people (Hamidi et al,2013), the elderly people (Moosavi et al, 2012) and immigrant groups (Cho et al, 2013).…”
Section: Discussionmentioning
confidence: 99%